Phosphate and IL-10 concentration as predictors of long-covid in hemodialysis patients: A Brazilian study - Corrêa, Hugo L.; Deus, Lysleine A.; Araújo, Thaís B.; Reis, Andrea L.; Amorim, Carlos E. N.; Gadelha, André B.; Santos, Rafael L.; Honorato, Fernando S.; Motta-Santos, Daisy; Tzanno-Martins, Carmen; Neves, Rodrigo V. P.; Rosa, Thiago S. (Frontiers in Immunology, 2022)
Background The global burden of persistent COVID-19 in hemodialysis (HD) patients is a worrisome scenario worth of investigation for the critical care of chronic kidney disease (CKD). We performed an exploratory post-hoc study from the trial U1111-1237-8231 with two specific aims: i) to investigate the prevalence of COVID-19 infection and long COVID symptoms from our Cohort of 178 Brazilians HD patients. ii) to identify whether baseline characteristics should predict long COVID in this sample. Methods 247 community-dwelling older (>60 years) patients (Men and women) undergoing HD (glomerular filtration rate < 15 mL/min/1.73m2) with arteriovenous fistula volunteered for this study. All patients presented hypertension and diabetes. Patients were divided in two groups: without long-COVID and with long-COVID. Body composition, handgrip strength, functional performance, iron metabolism, phosphate, and inflammatory profile were assessed. Patients were screened for 11-months after COVID-19 infection. Results were considered significant at P < 0.05. Results We found that more than 85% of the COVID-19 infected patients presented a severe condition during the infection. In our sample, the mortality rate over 11-month follow was relatively low (8.4%) when compared to worldwide (approximately 36%). Long COVID was highly prevalent in COVID-19 survivors representing more than 80% of all cases. Phosphate and IL-10 were higher in the long COVID group, but only phosphate higher than 5.35 mg/dL appears to present an increased prevalence of long COVID, dyspnea, and fatigue. Conclusion There was a high prevalence of COVID-19 infection and long COVID in HD patients from the Brazilian trial ‘U1111-1237-8231’. HD clinics should be aware with phosphate range in HD patients as a possible target for adverse post-COVID events.